(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Information technology is emerging demand and basic need of teaching-learning process that is a root of quality education. The present paper is an attempt to explore the socio economic status and various demographic factors that determining the attitude of secondary school teachers towards information technology. The study is descriptive in nature. Attitude Scale towards Information Technology for Teachers by Nasrin and Fatima Islahi and Socio-Economic Status Scale by O.P. Aggarwal are administered on a sample of 500 secondary school teachers of Fatehabad, Sirsa and Bhivani through purposive sampling technique. The result revealed a moderate significant relationship between socio economic status and attitude of secondary school teachers towards information technology. Further, the significant difference in attitude towards information technology has been found on the basis of gender, locality, nature of job, socio economic status and age of secondary school teachers.